Thioredoxin 1 is required for stress granule assembly upon arsenite-induced oxidative stress - Jovanovic, Bogdan; Eiermann, Nina; Talwar, Deepti; Boulougouri, Maria; Dick, Tobias P.; Stoecklin, Georg (Food and chemical toxicology, 2021)
Arsenic is a major water pollutant and health hazard, leading to acute intoxication and, upon chronic exposure, several diseases including cancer development. Arsenic exerts its pronounced cellular toxicity through its trivalent oxide arsenite (ASN), which directly inhibits numerous proteins including Thioredoxin 1 (Trx1), and causes severe oxidative stress. Cells respond to arsenic by inhibition of protein synthesis and subsequent assembly of stress granules (SGs), cytoplasmic condensates of stalled mRNAs, translation factors and RNA-binding proteins. The biological role of SGs is diverse and not completely understood; they are important for regulation of cell signaling and survival under stress conditions, and for adapting de novo protein synthesis to the protein folding capacity during the recovery from stress. In this study, we identified Trx1 as a novel component of SGs. Trx1 is required for the assembly of ASN-induced SGs, but not for SGs induced by energy deprivation or heat shock. Importantly, our results show that Trx1 is essential for cell survival upon acute exposure to ASN, through a mechanism that is independent of translation inhibition.
Gesehen am 04.11.2021